Impacts of the COVID-19 pandemic on the reality of Brazilian prisons - Oliveira, Hilderline Câmara de; Freita, Pedro Ramayana (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Since 2020, the world has been suffering the impacts of the new coronavirus, which has assumed the proportions of a global pandemic, a reality that also affects people deprived of liberty and public servants, who work within prison units in Brazil. Objective: To investigate and analyze the impacts and numbers of cases of covid-19 that affected the population deprived of liberty and civil servants in the reality of Brazilian prisons. Design: This research is exploratory and bibliographic in nature, using public domain data, authors and Brazilian legislation. Also, the time lapse of the data reflected here is until April 2021. Results: Information and notifications of cases of covid-19, which affect Brazilian prisons, are not widely publicized and do not follow the update as other segments of the population. In addition, some measures were taken by governments, including the suspension of visits, the purchase of hygiene kits, such as alcohol gel and others. Implications: In this scenario, there was evidence of the indifference and negligence of governments with people deprived of liberty, who do not have their rights enforced in most prisons in the country.